2011
DOI: 10.5423/rpd.2011.17.1.082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fusarium fujikuroi Isolated from Barnyard Grass and Possibility of Inoculum Source of Bakanae Disease on Rice

Abstract: Bakanae disease symptom were observed in barnyard grass in paddy field in Heanam, Jeonnam. The infected plants were blighted and white mass of spore were formed on the stem. Fusarium species were isolated from infected stem and the isolates were identified as Fusarium fujikuroi based on their morphological and molecular characteristics. The isolates of F. fujikuroi were assigned to reference of F. fujikuroi among related Fusarium species based on the translation elongation factor 1-alpha gene sequence. Pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The bakanae pathogen may also survive and be present as inoculum in overwintering plant debris or in soil ( Kanjanasoon, 1965 ; Su et al, 1979 ; Sunder, 1997 ). In addition, Choi et al (2011) isolated and confirmed the pathogenicity of the bakanae pathogen from barnyard grass, suggesting the possibility of barnyard grass as an alternative inoculum source.…”
Section: Epidemiology Of Bakanaementioning
confidence: 85%
“…The bakanae pathogen may also survive and be present as inoculum in overwintering plant debris or in soil ( Kanjanasoon, 1965 ; Su et al, 1979 ; Sunder, 1997 ). In addition, Choi et al (2011) isolated and confirmed the pathogenicity of the bakanae pathogen from barnyard grass, suggesting the possibility of barnyard grass as an alternative inoculum source.…”
Section: Epidemiology Of Bakanaementioning
confidence: 85%
“…They reported many monocotyledonous weeds in California rice fields should be evaluated as potential hosts of the bakanae pathogen in further study. Bakanae symptoms were observed in barnyard grass in a paddy field in Korea, in 2009 [ 74 ]. Fusarium species were isolated from the infected stem of barnyard grass and they were identified as F. fujikuroi .…”
Section: Host Range Of the Pathogenmentioning
confidence: 99%